2022
DOI: 10.3390/nano12050754
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Composites of Dextrin-Based Carbonate Nanosponges and Iron Oxide Nanoparticles with Potential Application in Targeted Drug Delivery

Abstract: Magnetically driven nanosponges with potential application as targeted drug delivery systems were prepared via the addition of magnetite nanoparticles to the synthesis of cyclodextrin and maltodextrin polymers crosslinked with 1,1′-carbonyldiimidazole. The magnetic nanoparticles were obtained separately via a coprecipitation mechanism involving inorganic iron salts in an alkaline environment. Four composite nanosponges were prepared by varying the content of magnetic nanoparticles (5 wt% and 10 wt%) in the cyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…The NSs–MPH and NSs–CUR complexes also show a spherical structure, and an increase in size to 150 nm after drug loading, with respect to native NSs. This could probably be attributed to intermolecular interactions occurring in the NSs–drug complexes, as reported in previous studies [ 33 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…The NSs–MPH and NSs–CUR complexes also show a spherical structure, and an increase in size to 150 nm after drug loading, with respect to native NSs. This could probably be attributed to intermolecular interactions occurring in the NSs–drug complexes, as reported in previous studies [ 33 , 46 , 47 ].…”
Section: Resultssupporting
confidence: 58%
“…NSs may form inclusion compounds (ICs) with different molecules, by using the multiple supramolecular sites that are formed in the cross-linking reaction, and can be used as drug-delivery systems, as previously reported [ 5 , 28 , 29 , 30 , 31 ]. In recent years, several studies have shown that the decoration of NSs with metal nanoparticles can improve the usefulness and properties of the polymer, namely magnetite [ 10 , 32 , 33 ], silver [ 34 , 35 ], or gold nanoparticles [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the oral bioavailability of avanafil and dapoxetin was improved by applying cyclodextrin-based nanosponges [ 67 ]. Magnetic nanosponges have shown great potential for targeted drug delivery as well [ 68 ]. These nanosystems were prepared after the addition of magnetite nanomaterial to the polymers of cyclodextrin and maltodextrin, crosslinked with 1,1′-carbonyldiimidazole.…”
Section: Drug Delivery and Cancer Therapymentioning
confidence: 99%
“…These nanosystems were prepared after the addition of magnetite nanomaterial to the polymers of cyclodextrin and maltodextrin, crosslinked with 1,1′-carbonyldiimidazole. One study reported the design of magnetic nanosponges for the targeted delivery of doxorubicin with the loading capacity of ~3 wt%, wherein the loaded anticancer drug could be released with sustained kinetics over a prolonged period of time [ 68 ].…”
Section: Drug Delivery and Cancer Therapymentioning
confidence: 99%
“…Drug detection is essential in the monitoring of drug molecules in bio-fluids and plays an important role in drug quality control [ 1 , 2 ]. Paracetamol, also known as acetaminophen, is one of the most popular analgesics/antipyretics and has been applied in effective treatment of pain and fever in adults and children [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%